The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/nbm.4869
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance quantification of skeletal muscle lipid infiltration in a humanized mouse model of Duchenne muscular dystrophy

Abstract: Rodent models of Duchenne muscular dystrophy (DMD) often do not recapitulate the severity of muscle wasting and resultant fibro‐fatty infiltration observed in DMD patients. Having recently documented severe muscle wasting and fatty deposition in two preclinical models of muscular dystrophy (Dysferlin‐null and mdx mice) through apolipoprotein E (ApoE) gene deletion without and with cholesterol‐, triglyceride‐rich Western diet supplementation, we sought to determine whether magnetic resonance imaging and spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The triceps brachii is one of the muscles that show the most exacerbation, along with the gastrocnemius muscle, whereas only a mild exacerbation of mdx-associated cardiac dysfunction was observed (Table 2). Advanced MRI/MRS imaging confirmed that the extreme fatty tissue deposition of mdx/ApoE KO mice resembles that observed clinically in DMD muscle but typically absent in mdx mice [67]. Surprisingly, no exacerbation of diaphragm fibrosis was observed in mdx/ApoE KO mice.…”
Section: Dmd Modeling and Lipoprotein Metabolism -The Mdx/apoe Ko Mousesupporting
confidence: 53%
“…The triceps brachii is one of the muscles that show the most exacerbation, along with the gastrocnemius muscle, whereas only a mild exacerbation of mdx-associated cardiac dysfunction was observed (Table 2). Advanced MRI/MRS imaging confirmed that the extreme fatty tissue deposition of mdx/ApoE KO mice resembles that observed clinically in DMD muscle but typically absent in mdx mice [67]. Surprisingly, no exacerbation of diaphragm fibrosis was observed in mdx/ApoE KO mice.…”
Section: Dmd Modeling and Lipoprotein Metabolism -The Mdx/apoe Ko Mousesupporting
confidence: 53%
“…The regeneration of limb muscles has been shown to restore normal muscle structure, whereas the DIA is subject to progressive degeneration and fibrosis formation and shows a pathology similar to that of DMD patients [30,31]. However, it is noteworthy that the mdx mouse fails to fully replicate the severity of the fibro-fatty pathology seen in human DMD [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the non-statin cholesterol-lowering agent ezetimibe showed promise in mouse models of dystrophinopathy and dysferlinopathy 43 . Increased lipids are also not a solution, as they exacerbate the muscular dystrophy phenotype 44,45 . These studies indicate that direct manipulation of lipid levels does not clearly show promise, at this time, as a therapeutic strategy for muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%